Toxicity of traditional and soluble film automatic dishwashing tablets. (April 2020) - Day, R; Bradberry, SM; Sandilands, EA; Thomas, SHL; Thompson, JP; Vale, JA
Introduction: Detergents used in automatic dishwashing machines are of two main types: traditional tablets that require removal from an external wrapper and newer soluble film tablets. Objective: To determine the toxicity of automatic dishwashing tablets. Methods: Telephone enquiries to the UK National Poisons Information Service were analysed for the period January 2008 to June 2019. Results: Ingestion : Ingestion was involved in 798 traditional tablet exposures and 725 soluble film exposures. Clinical features (Poisoning Severity Score ≥ 1) developed in 22.2% of patients ingesting traditional tablets and in 28.8% ingesting soluble film tablets; moderate or severe toxicity was rare (<0.5% for both traditional and soluble film tablets). Children (≤5 years) significantly ( p < 0.0001) more often developed features following ingestion of soluble film ( n = 193, 28.2%) than traditional tablets ( n = 134, 19.1%). In contrast, adults more often developed features following ingestion of traditional than soluble film tablets, although this difference was not statistically significant. Eye exposure : The eye was involved in only 26 of 1539 exposures; 17 of 26 exposures resulted in ocular features. The most commonly reported features were conjunctivitis, eye pain and blurred vision, although one patient sustained a corneal abrasion and developed loss of vision. Skin exposure : Thirty-four of 1539 exposures involved the skin but only 3 developed dermal features which were minor. Conclusions: Children (≤5 years) significantly more often developed features following ingestion of soluble film than traditional tablets, although the likelihood of a child developing features was relatively low (<30%) and features that did develop were almost always mild. In contrast, adults more often developed features following the ingestion of traditional than soluble film tablets. Overall, the eye was involved in only 1.7% of exposures and only one patient sustained a corneal abrasion.